Discordant courses of COVID‐19 in a cohabiting couple of lung transplant recipients. Issue 1 (31st July 2020) - Desmazes‐Dufeu, Nadine; Coltey, Bérengère; Amari, Lyria; Gouitaa, Marion; Touzery, Camille; Reynaud‐Gaubert, Martine; Chanez, Pascal; Cassir, Nadim
Abstract: COVID‐19 is a novel infectious disease caused by SARS‐CoV‐2 that emerged in late 2019 and which is now a pandemic. Solid organ transplant recipients are perceived to be at increased risk of severe COVID‐19 due to their chronic use of immunosuppressive drugs (ISDs) and to their associated conditions. Scarce data are available on the optimized management of ISDs in these patients and on its impact on presentation, clinical course, viral shedding, and outcome. We report here two cases of COVID‐19 in a cohabiting couple of lung transplant recipients for cystic fibrosis, who had different ISDs management and who developed discordant courses of their disease. Our findings suggest that the degree of their immunosuppression might be a reason for their different course and that ISDs might prove partially protective.